M'sia need not take it to ICJ - Daily Express, (KK) (Daily Ekspress (kk), 2013)
KUALA LUMPUR: There is no need for Malaysia to bring the issue of Sabah's rights to the International Court of Justice (ICJ) as historical and non-historical facts clearly show that it is a sovereign state of Malaysia, said historian Prof Emeritus Dr Ranjit Singh of Universiti Utara Malaysia.